If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10(y + -8) = -30 Reorder the terms: 10(-8 + y) = -30 (-8 * 10 + y * 10) = -30 (-80 + 10y) = -30 Solving -80 + 10y = -30 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '80' to each side of the equation. -80 + 80 + 10y = -30 + 80 Combine like terms: -80 + 80 = 0 0 + 10y = -30 + 80 10y = -30 + 80 Combine like terms: -30 + 80 = 50 10y = 50 Divide each side by '10'. y = 5 Simplifying y = 5
| 11x+2x=91 | | 3(n-7)=-7 | | 14-2(4x-8)=6 | | 6(x+3)+6=42 | | 2x+3=5x+8 | | 5r^2-20r-9=6 | | 3w(11w+8)= | | 5r^2-20r-9=0 | | 13.62+.13(x+3)=14.37-.09x | | xsquare(x+5)(x-5)=0 | | 1600x=20 | | 3y+17=62 | | y+19=192 | | f(-6)=7-2x | | 4x+14=5x | | 2x=6(2x-2)-5 | | 13.62+.13(x+3)=14.37+.09x | | 3(3+1)=(9-2x) | | 6n=(n+5) | | 30=-8x+2(x-6) | | y=mx+bfindx | | x^1/4=2 | | 5x-15=2x+20 | | 90+3+x+x-8=180 | | 10n-0.75=0.1n-0.375 | | 2-7g=2-g | | 2e^3x-9=0 | | 12a=3a+2.5a+a | | -1=6x-31 | | 15.93+.09(x+3)=16.43-.13x | | -3(3y-7)+2(2y+8)= | | 2[-2(4x+5)+4(3x-4)]= |